2013
DOI: 10.1089/tmj.2012.0290
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Event Detection in Lung Transplant Recipients Based on Home Monitoring of Spirometry and Symptoms

Abstract: Objective: The goal of this study was to develop, implement, and test an automated decision system to provide early detection of clinically important bronchopulmonary events in a population of lung transplant recipients following a home monitoring protocol. Subjects and Methods: Spirometry and other clinical data were collected daily at home by lung transplant recipients and transmitted weekly to the study data center. Decision rules were developed using wavelet analysis of declines in spirometry and increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…[12][13][14] A liver transplant program in Cincinnati OH is conducting a pilot study on the use of tablet-based real-time monitoring in the early post-operative period, including vital signs, glucose levels, weight, and contact with the healthcare team. [12][13][14] A liver transplant program in Cincinnati OH is conducting a pilot study on the use of tablet-based real-time monitoring in the early post-operative period, including vital signs, glucose levels, weight, and contact with the healthcare team.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] A liver transplant program in Cincinnati OH is conducting a pilot study on the use of tablet-based real-time monitoring in the early post-operative period, including vital signs, glucose levels, weight, and contact with the healthcare team. [12][13][14] A liver transplant program in Cincinnati OH is conducting a pilot study on the use of tablet-based real-time monitoring in the early post-operative period, including vital signs, glucose levels, weight, and contact with the healthcare team.…”
Section: Discussionmentioning
confidence: 99%
“…This has been examined in prior studies and shown to be a feasible alternative to manual review to detect changes in pulmonary function. [12][13][14] A liver transplant program in Cincinnati OH is conducting a pilot study on the use of tablet-based real-time monitoring in the early post-operative period, including vital signs, glucose levels, weight, and contact with the healthcare team. 15 The use of these technologies may also facilitate data gathering for clinical outcome studies in transplant recipients and is something our program will be exploring in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Future mHealth interventions should take advantage of technologies that automate the process of data recording and tracking, such as electronic blood pressure cuffs and spirometers. Evidence from lung transplant recipients indicates that such features have high patient acceptability (27, 28). Moreover, mHealth interventions should refine their decision-support features so that patients can receive real-time feedback about all health data they record.…”
Section: Discussionmentioning
confidence: 99%
“…Although all LTR receive discharge instructions for detecting and reporting critical condition changes during home self-monitoring, LTR find it challenging to identify the thresholds of critical values for multiple health indicators, for example, the lower or upper limits of blood pressures, and to recognize critical changes from their own personal baselines [9]. Considering the amount of self-monitoring data generated by all LTR, it would be too time-consuming for clinicians to track and screen critical values for each LTR [10]. Patient engagement in self-management is important for the improvement of health outcomes [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Electronic spirometry systems have been reported to be reliable and valid for LTR health self-monitoring [10,13–15]. However, most electronic spirometry systems have been designed to send self-monitoring data to clinicians for interpretation, and do not provide decision support for LTR [1519].…”
Section: Introductionmentioning
confidence: 99%